Kinetic and kinematic analysis of recurve archery shooting technique - Simsek, D.; Cerrah, A. O.; Ertan, H.; Soylu, A. R. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The study investigated shooting techniques of the archers with kinetic and kinematic methods. Twenty-seven archers of different skill levels have been involved into the current study to investigate both muscular activation strategies of nine muscles and some kinematic data on drawing hand side. A statistical significant difference (p0.05) in the time-dependent exchange values of the angle of the joints, a difference was detected in the graphical sense. Elite archers use distal muscles less but proximal and axial muscles more, and mid-level and novice archers use distal muscles more to pull the bowstring. This was interpreted to be the most important factor affecting the horizontal oscillation (lateral diflection) of bowstring.